Olvasóvá nevelés újszülött kortól kezdve: A gyerekkönyvek és az irodalom szerepe a 0–3 éves gyerekek életében - Szinger, Veronika (Studia Litteraria, 2019)
Even before the formal literacy education most of the children meet literacy in a spontaneous way. Emergent literacy is the term used to describe young children’s developing literacy skills before formal reading and writing instruction in school. Much research has demonstrated that the home environment serves as an important influence in the development of emergent literacy skills in young children. Family literacy refers to literacyrelated processes, for example when family members engage in shared story reading which positively influences young children’s motivations to read. Since babies and toddlers (children under three) are dependent on their parents and carers for access to books, developmentally appropriate reading materials (board and tactile books, picture books and storytelling books nursery rhymes), are recommended which are of high quality, age appropriate, challenging without frustrating, worthy of attention for parents and carers.